1998
DOI: 10.1002/hep.510270139
|View full text |Cite
|
Sign up to set email alerts
|

Management of adult patients with ascites caused by cirrhosis†

Abstract: Ascites is the most common of the major complications of cirrhosis. The development of ascites is an important landmark in the natural history of cirrhosis and has been proposed as an indication for liver transplantation. The initial evaluation of a patient with ascites should include a history, physical evaluation, and abdominal paracentesis with ascitic fluid analysis. Treatment should consist of abstinence from alcohol, sodium restricted diet, and diuretics. This regimen is effective in Ϸ90% of patients. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
135
1
10

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(148 citation statements)
references
References 71 publications
2
135
1
10
Order By: Relevance
“…The use of albumin has been contested by the Practice Guidelines Committee of the American Association for the Study of Liver Diseases. 34 There have been 5 randomized controlled trials comparing volume expansion with albumin with other forms of plasma expanders, including dextrans, collagen-based colloids, and hydroxyethyl starch. [35][36][37][38][39] All studies have shown that synthetic plasma expanders are as effective as albumin at preventing the clinical complications of paracentesis, namely hyponatremia or renal impairment.…”
Section: Paracentesismentioning
confidence: 99%
“…The use of albumin has been contested by the Practice Guidelines Committee of the American Association for the Study of Liver Diseases. 34 There have been 5 randomized controlled trials comparing volume expansion with albumin with other forms of plasma expanders, including dextrans, collagen-based colloids, and hydroxyethyl starch. [35][36][37][38][39] All studies have shown that synthetic plasma expanders are as effective as albumin at preventing the clinical complications of paracentesis, namely hyponatremia or renal impairment.…”
Section: Paracentesismentioning
confidence: 99%
“…In addition, the many dietary restrictions used to control symptoms and specifi c complications, such as ascites and hepatic encephalopathy, aggravate the nutritional status, predisposing the patients to infections and worsening of the functional hepatic status (21,34,37) .…”
Section: Introductionmentioning
confidence: 99%
“…The AASLD thus recommends testing of ascitic fluid for cell count and differential count, but not necessarily culture, for patients undergoing serial outpatient therapeutic paracentesis, each time the fluid is removed [4]. Given the low prevalence of SBP in asymptomatic patients, the question is whether we need to undertake ascitic fluid cell count routinely in all cases of paracentesis.…”
mentioning
confidence: 99%